PENGARUH MANAJEMEN KOPERASI DALAM MENINGKATKAN SISA HASIL USAHA (SHU) DI KOPERASI (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2019)
This study aims to determine whether SEHATI credit cooperatives have implemented good and correct cooperative management in an effort to improve SHU (remaining operating results). This study took primary data in a questionnaire that was distributed to members. At SEHATI Cooperative, the focus is on the East Jakarta cakung branch office cooperative with 265 active members. The data were then analyzed using the Validity and Reliability Test, and the Coefficient of Determination Test, the t Test, to test the research hypothesis. Based on the T test, the influence of cooperative management together has a positive effect on residual business results. Y).